Islam and Art: by Dr. Lois Lamya al Faruqi Published by the National Hijm Council, Islamabad 1405 A.H., 1985,236 pp. and 60 plates, $6.00 (American Journal of Islam and Society, 1986)
I met Dr. Lois Lamya al Faruqi last March, while I was giving a lectureon Arabic calligraphy at the University of Pennsylvania in Philadelphia. I hadcorresponded with her previously and had been impressed by her graciousnessand her insight into the complex field of Islamic art. Now, here she and herhusband were, and I was pleased to have these bright lights of the Muslimcommunity in my audience. At the end of my remarks, someone asked theinevitable question, "What is the significance, the symbolism of the designsused to highlight a calligraphic piece?" I replied that, while some Islamicdesigns have their origins in the material world, they become abstracted andstylized but do not take on additional symbolic meaning. In other words, Islamicart, at its best, does not depend on visual symbols as clues to its meaning.A flower Wing remains a flower drawing, no matter how abstract it becomes.Dr. Faruqi's was interested in my interpretation and, I think somewhat amused.As she left that evening, I saw a definite twinkle in her eye, and I feltI had found a congenial colleague. Two weeks later, I received an autographedcopy of Islam and Art from her. I never saw her again.I am pleased to have this opportunity to review this volume, Dr. Faruqi'slast published work. Let me make my own position clear: I am neither anacademician nor a genuine scholar of Islamic art. Rather, I approach the subjectas a practitioner; therefore, my interest in Islamic art-and in this book- isat once personal, practical, and professional.Why do the arts of the Muslim peoples-and by arts, I include graphicarts, architecture, crafts, and music -develop with such obvious consistencyfrom people to people, and in such a straight line from their inception to thepresent? This question has baffled scholars for at least a century. Dr. Faruqi'sinsight guides the reader in the direction of a true answer, yet it is an answereach of us must experience for ourselves, through study and contemplation.In short, Dr. Faruqi's answer to this central question is that the arts ofthe Muslim peoples did not develop by chance, but rather, as an attempt toexpress by various media the Quranic doctrine of tawhid, the immense ...